Disrespect and abuse as a predictor of postnatal care utilisation and maternal-newborn well-being: a mixed-methods systematic review. Issue 4 (21st April 2021) - Minckas, Nicole; Gram, Lu; Smith, Colette; Mannell, Jenevieve
Abstract : Introduction: Globally, a substantial number of women experience abusive and disrespectful care from health providers during childbirth. As evidence mounts on the nature and frequency of disrespect and abuse (D&A), little is known about the consequences of a negative experience of care on health and well-being of women and newborns. This review summarises available evidence on the associations of D&A of mother and newborns during childbirth and the immediate postnatal period (understood as the first 24 hours from birth) with maternal and neonatal postnatal care (PNC) utilisation, newborn feeding practices, newborn weight gain and maternal mental health. Methods: We conducted a systematic review of all published qualitative, quantitative and mixed-methods studies on D&A and its postnatal consequences across all countries. Pubmed, Embase, Web of Science, LILACS and Scopus were searched using predetermined search terms. Quantitative and qualitative data were analysed and presented separately. Thematic analysis was used to synthesise the qualitative evidence. Results: A total of 4 quantitative, 1 mixed-methods and 16 qualitative studies were included. Quantitative studies suggested associations between several domains of D&A and use of PNC as well as maternal mental health. Different definitions of exposure meant formal meta-analysis was not possible. Three main themes emerged from the qualitative findings associated with PNC utilisation: (1) women's direct experiences; (2) women's expectations and (3) women's agency. Conclusion: This review is the first to examine the postnatal effect of D&A of women and newborns during childbirth. We highlight gaps in research that could help improve health outcomes and protect women and newborns during childbirth. Understanding the health and access consequences of a negative birth experience can help progress the respectful care agenda.